MENGINISIASI PEMBENTUKAN BUMDES PULO PANJANG SEBAGAI TULANG PUNGGUNG PENINGKATAN EKONOMI MASYARAKAT SEKITAR - Abdul Bahits; Muhamad Nawab Alawi; Siti Chairunissa; Aria Luska; Elisabeth Chyntia Dewi; Sulis Wahyuningsih (Yayasan Education and Social Center, 2021)
Pulo Panjang Village is one of the developing villages, the problems faced by Pulo Panjang Village in terms of MSMEs are rarely in demand by producers because they think the processing is complicated and requires much capital as a result of many business actors who go out of business. Therefore, the increase in the economy of rural communities cannot be implemented by one party only but must be through coordination with other parties both with the government and the community as a whole. There is much potential that can be explored. One of them is the BUMDesa program. BUMDES was born as a new approach to improve the village economy based on the needs and potential of the village. Bumdes management is fully implemented by the village community, namely from the village, the village, and the village. BUMDES is a community economic institution. When viewed from its potential, this village has excellent potential for establishing BUMDES as a reservoir for community economic activities and public service institutions. Therefore, the formation of BUMDES is expected to be a breakthrough for the people of Pulo Panjang village as the Backbone of Community EconomicImprovement